2000
DOI: 10.1021/jf000342o
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Aflatoxin in Pistachios. 7. Sequential Sampling

Abstract: Sequential sampling for aflatoxin testing in pistachios is evaluated using the aflatoxin distribution and Monte Carlo results previously obtained (J. Agric. Food Chem. 1999, 47, 3771-3775). The sequential protocol is modeled on the current EU test protocol by applying a three-step sampling, using 10, 20, and 30 kg sample averages. An acceptance level of 15 ng/g of total aflatoxin, under consideration for U.S. standards, is applied. Optimization leads to indifference regions of 2-30 ng/g for the first two steps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Studies have demonstrated that aflatoxins and other mycotoxins are seldom uniformly distributed throughout most food and feed commodities, their occurrence being uneven and sporadic. It is estimated that only very few nuts are responsible for the overall aflatoxin concentration of a lot (as few as one nut in 10 5 ) 22 and the actual level of contamination in these nuts may span up to eight orders of magnitude. Whitaker et al note that the extreme range in aflatoxin concentrations among individual peanut kernels in a contaminated lot and that variation among replicated samples tended to be large.…”
Section: Case Study Of Aflatoxins In Pistachio Nutsmentioning
confidence: 99%
“…Studies have demonstrated that aflatoxins and other mycotoxins are seldom uniformly distributed throughout most food and feed commodities, their occurrence being uneven and sporadic. It is estimated that only very few nuts are responsible for the overall aflatoxin concentration of a lot (as few as one nut in 10 5 ) 22 and the actual level of contamination in these nuts may span up to eight orders of magnitude. Whitaker et al note that the extreme range in aflatoxin concentrations among individual peanut kernels in a contaminated lot and that variation among replicated samples tended to be large.…”
Section: Case Study Of Aflatoxins In Pistachio Nutsmentioning
confidence: 99%
“…B. in einer Partie Nüsse, Gewürze oder auch Trockenfrüchte kann sehr heterogen sein. Es kommen punktuell sehr hohe und an anderer Stelle sehr geringe bis hin zu nicht nachweisbaren Belastungen vor (Schatzki, 2000;Whitaker et al, 1993Whitaker et al, und 2005, wodurch die Probenahme einen entscheidenden Beitrag bei der Identifizierung hoher Mykotoxinbelastungen leistet und daher als separater Einzelpunkt bei der Gegenüberstellung der Analyseverfahren Berücksichtigung findet. (Food and Agriculture Organization, 2004).…”
Section: Introductionunclassified